Tingkat pengetahuan dan sikap remaja tentang seks bebas siswa kelas X dan XI SMK Bina Harapan Sleman Tahun 2015 - Ika Novitasari Kardiya; Dwiana Estiwidani; Munica Rita Hernayanti (Poltekkes Kemenkes Yogyakarta, 2016)
Based on a survey BKKBN, in Indonesia 63 million people teenagers aged 10-24 years behave unsoundly which is associatedpremarital sex. Yogyakarta there are 62,7% of teenagers junior and senior high school, not a virgin. In 2014 cases of HIV/AIDS in Sleman District ranked second after the city of Yogyakarta is 112 cases. This study purpose to determine the level of knowledge and attitudes of teenagers about free sex students X and XI grade's SMK Bina Harapan 2015. The method of this research is descriptive with the approach cross-sectional. The collection of data using a questionnaire the level of knowledge and attitudes of teenagers about free sex. The subject of research a number of 76 respondents.the results of research shows the level of knowledge about free sex 43,42% respondents having good knowledge, knowledge about understanding 35,53%, knowledge about forms of free sex 52,64%, knowledge about factors that affect 52,64%, knowledge about consequences 50%. Attitudes about free sex respondents who don't support 53,95%. In conclusion the level ofknowledge about the free sex majority of respondents having good. Attitudes about free sex the majority of respondents didn'tsupport free sex.